Expression dynamics of genes in the hypothalamic-pituitary-thyroid (HPT) cascade and their responses to 3,3′,5-triiodo-l-thyronine (T3) highlights potential vulnerability to thyroid-disrupting chemicals in zebrafish (Danio rerio) embryo-larvae - Parsons, Aoife E.; Lange, Anke; Hutchinson, Thomas H.; Miyagawa, Shinichi; Iguchi, Taisen; Kudoh, Tetsuhiro; Tyler, Charles R. (Aquatic toxicology, 2020)
•Genes in the HPT axis were dynamically expressed in zebrafish early life stages.•Exposure to T3 disrupted the thyroid axis of zebrafish at multiple mRNA transcripts.•The effect of T3 on examined mRNA transcripts was tissue- and life stage-specific.•Environmental chemicals may disrupt the development of TH-dependent tissues. Some chemicals in the environment disrupt thyroid hormone (TH) systems leading to alterations in organism development, but their effect mechanisms are poorly understood. In fish, this has been limited by a lack of fundamental knowledge on thyroid gene ontogeny and tissue expression in early life stages. Here we established detailed expression profiles for a suite of genes in the hypothalamic-pituitary-thyroid (HPT) axis of zebrafish (Danio rerio) between 24–120 h post fertilisation (hpf) and quantified their responses following exposure to 3,3’,5-triiodo-L-thyronine (T3) using whole mount in situ hybridisation (WISH) and qRT-PCR (using whole-body extracts). All of the selected genes in the HPT axis demonstrated dynamic transcript expression profiles across the developmental stages examined. The expression of thyroid receptor alpha (thraa) was observed in the brain, gastrointestinal tract, craniofacial tissues and pectoral fins, while thyroid receptor beta (thrb) expression occurred in the brain, otic vesicles, liver and lower jaw. The TH deiodinases (dio1, dio2 and dio3b) were expressed in the liver, pronephric ducts and brain and the patterns differed depending on life stage. Both dio1 and dio2 were also expressed in the intestinal bulb (96–120 hpf), and dio2 expression occurred also in the pituitary (48–120 hpf). Exposure of zebrafish embryo-larvae to T3 (30 and 100 μg L−1) for periods of 48, 96 or 120 hpf resulted in the up-regulation of thraa, thrb, dio3b, thyroid follicle synthesis proteins (pax8) and corticotropin-releasing hormone (crhb) and down-regulation of dio1, dio2, glucuronidation enzymes (ugt1ab) and thyroid stimulating hormone (tshb) (assessed via qRT-PCR) and responses differed across life stage and tissues. T3 induced thraa expression in the pineal gland, pectoral fins, brain, somites, gastrointestinal tract, craniofacial tissues, liver and pronephric ducts. T3 enhanced thrb expression in the brain, jaw cartilage and intestine, while thrb expression was suppressed in the liver. T3 exposure suppressed the transcript levels of dio1 and dio2 in the liver, brain, gastrointestinal tract and craniofacial tissues, while dio2 signalling was also suppressed in the pituitary gland. Dio3b expression was induced by T3 exposure in the jaw cartilage, pectoral fins and brain. The involvement of THs in the development of numerous body tissues and the responsiveness of these tissues to T3 in zebrafish highlights their potential vulnerability to exposure to environmental thyroid-disrupting chemicals.